KEYNOTE‐032: A Randomized Phase I Study of Pembrolizumab in Chinese Patients with Advanced Non‐Small Cell Lung Cancer. (5th March 2020) - Ma, Yuxiang; Fang, Wenfeng; Zhang, Yang; Yang, Yunpeng; Hong, Shaodong; Zhao, Yuanyuan; Xie, Shuang; Ge, Jun; Zhou, HaoJin; Zhao, Hongyun; Zhang, Li
Abstract: Trial Information: ClinicalTrials.gov Identifier: NCT02835690 Sponsor: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Principal Investigator: Li Zhang IRB Approved: Yes Click here to access other published clinical trials . Lessons Learned: Results of the KEYNOTE‐032 study showed that the safety and pharmacokinetic profiles of pembrolizumab in Chinese patients were comparable with those observed in international studies, and antitumor activity was encouraging. These data support further evaluation of pembrolizumab to improve clinical outcomes in Chinese patients with advanced non‐small cell lung cancer. Background: The KEYNOTE‐032 study evaluated pembrolizumab pharmacokinetics and clinical outcomes in Chinese patients with locally advanced and/or metastatic non‐small cell lung cancer (NSCLC) and prior treatment failure and/or ineligibility for standard therapy. Methods: Patients were randomized 1:1:1 to pembrolizumab 2 mg/kg, 10 mg/kg, or 200 mg every 3 weeks (up to 35 cycles). Safety and pharmacokinetics were primary endpoints; antitumor activity was a secondary endpoint. Results: A total of 42 of 44 randomized patients received pembrolizumab treatment (2 mg/kg, n = 14; 10 mg/kg, n = 13; 200 mg, n = 15). Treatment‐related adverse events (AEs) occurred in 29 of 42 (69%) patients (grade 3–4, 4/42 [10%]); 5 (12%) had immune‐mediated AEs and infusion reactions. Pembrolizumab single dose half‐life following 2 mg/kg, 10 mg/kg, and 200 mg was 15.1, 15.8, and 12.3 days, respectively. Serum exposure at the doses studied (range, 2–10 mg/kg) was approximately linear; steady‐state area under the curve0–21 days (95% confidence interval [CI]) was 730.9 (627.4–851.6), 2, 819.2 (2, 009.4–3, 955.4), and 931.0 (724.4–1, 196.6) μgday/mL, respectively. After 7.9 (range, 0.7–13.1) months median follow‐up overall, objective response rate was 14.3% (95% CI, 5.4%–28.5%); median progression‐free survival was 2.1 (95% CI, 2.1–4.2) months, and median overall survival was not reached (95% CI, 6.6 months–not reached). Conclusion: Pembrolizumab had manageable toxicity, linear serum exposure, and encouraging antitumor activity in Chinese patients with advanced NSCLC.